Critical Expressivism Theory and Practice in the Composition Classroom - Roeder, Tara; Gatto, Roseanne (Open textbook library., 2014)
Critical Expressivism is an ambitious attempt to re-appropriate intellectual territory that has more often been charted by its detractors than by its proponents. Indeed, as Peter Elbow observes in his contribution to this volume, "As far as I can tell, the term 'expressivist' was coined and used only by people who wanted a word for people they disapproved of and wanted to discredit." The editors and contributors to this collection invite readers to join them in a new conversation, one informed by "a belief that the term expressivism continues to have a vitally important function in our field."